Effect of different types of microplastics on the vital activity of bloodsucking mosquitoes Aedes aegypti L. (Diptera: Culicidae) - Simakova, Anastasia V.; Babkina, Irina B.; Varenitsina, Anna A.; Yulia V. Andreeva; Vorobiev, Egor D.; Yulia A. Frank (Altai State University, 2024)
We have experimentally investigated the effect of three different types of microplastics (high-density polyethylene, polypropylene and polystyrene) on body weight, metamorphosis rate and mortality of bloodsucking mosquitoes Aedes aegypti (Linnaeus 1762), vectors of protozoal and helminthic diseases of humans and animals. Supplementation of the diet with polypropylene was found to have no effect on mosquito weight at all life stages, while the addition of high-density polyethylene and polystyrene promoted a decrease in larval weight and an increase in adult weight (p < 0.05). Ingestion of high-density polyethylene by larvae increased pupal weight and decreased adult weight compared to the control, whereas no such effect was found for polypropylene and polystyrene. High-density polyethylene and polystyrene did not affect mosquito mortality at all stages, but there was a tendency for polypropylene to have an adverse effect on pupal and adult survival. The survival rate of mosquitoes at all life stages in both the control and experimental groups was generally quite high. Supplementation of the diet with different types of plastics did not affect the metamorphosis rate at all stages of mosquito development and was comparable in both the control and experimental groups. The experiments revealed no significant effect of different types of plastics on the vital activity of Ae. aegypti . Only high-density polyethylene microparticles were found to significantly affect mosquito body weight, yet this was opposite at the pupal and adult stages.